Cryptococcal Meningitis and Anti-virulence Therapeutic Strategies - Vu, Kiem; Garcia, Javier A.; Gelli, Angie (Frontiers in Microbiology, 2019)
Fungal infections of the central nervous system are responsible for significant morbidity and mortality. Cryptococcus neoformans (Cn) is the primary cause of fungal meningitis. Infection begins in the lung after inhalation of fungal spores but often spreads to other organs, particularly the brain in immunosuppressed individuals. Cn’s ability to survive phagocytosis and endure the onslaught of oxidative attack imposed by the innate immune response facilitates dissemination to the central nervous system (CNS). Despite the success of Cn at bypassing innate immunity, entry into the heavily protected brain requires that Cn overwhelm the highly restricted blood-brain barrier (BBB). This is a formidable task but mounting evidence suggests that Cn expresses surface-bound and secreted virulence factors including urease, metalloprotease and hyaluronic acid that can undermine the BBB. In addition, Cn can exploit multiple routes of entry to gain access to the CNS. In this review, we discuss the cellular and molecular interface of Cn and the BBB, and we propose that the virulence factors mediating BBB crossing could be targeted for the development of anti-virulence drugs aimed at preventing fungal colonization of the CNS.